2013
DOI: 10.1089/hum.2013.2512
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sarcoplasmic Reticulum Calcium ATPase by Gene Therapy

Abstract: Although pharmacologic therapies have provided gains in reducing the mortality of heart failure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 100 publications
(89 reference statements)
1
26
0
1
Order By: Relevance
“…In contrast to the strong effect of LRP1 deficiency on SERCA2, LRP1 deficiency does not prevent the downregulatory effect of hypoxia on NCX-1 and CAV1.2. These results support a pivotal role of SERCA2 on the maintenance of calcium metabolism and are in agreement with the enormous potential of SERCA2 restoration by pharmacological action or gene delivery in the treatment of heart failure [37][38][39].…”
Section: Impact Of Lrp1 Deficiency On Calcium-handling Proteins and Csupporting
confidence: 87%
“…In contrast to the strong effect of LRP1 deficiency on SERCA2, LRP1 deficiency does not prevent the downregulatory effect of hypoxia on NCX-1 and CAV1.2. These results support a pivotal role of SERCA2 on the maintenance of calcium metabolism and are in agreement with the enormous potential of SERCA2 restoration by pharmacological action or gene delivery in the treatment of heart failure [37][38][39].…”
Section: Impact Of Lrp1 Deficiency On Calcium-handling Proteins and Csupporting
confidence: 87%
“…Of the multiple regulators of calcium handling in heart failure, SERCA2 has received significant attention because of its primary role in calcium re-uptake to the sarcoplasmic reticulum. Indeed, SERCA2's activity is diminished in the failing heart 45 , and adenoviral administration of SERCA2a in failing cardiomyocytes improves contractility in various animal models of HF 46-49 . The resulting clinical trial, CUPID, demonstrated safety 50 and efficacy 51 of intracoronary infusion of recombinant AAV1/SERCA2a.…”
Section: Gene/molecular Therapymentioning
confidence: 99%
“…Under physiological conditions, this inhibition is relieved by either micromolar Ca 2+ or by phosphorylation of PLB, primarily by protein kinase A (PKA) at S16 [5]. Recent gene therapies targeting increased SERCA activity show promise for alleviation of heart failure [6]. Ablation of PLB or introduction of phosphomimetic mutant S16E-PLB suppress progression of heart failure in animal models [7,8,9].…”
Section: Introductionmentioning
confidence: 99%